2014
DOI: 10.1136/archdischild-2013-304741
|View full text |Cite
|
Sign up to set email alerts
|

Toxic shock syndrome surveillance in UK children

Abstract: Streptococcal TSS was as frequent as staphylococcal TSS, contrasting with previous literature. Children with streptococcal TSS had a higher mortality than those with staphylococcal TSS (28% vs 0%; p<0.05). Recommended immunomodulatory agents (IVIG and clindamycin) were underused. This study highlights the need for a guideline to improve management of TSS in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 31 publications
6
34
3
1
Order By: Relevance
“…The most striking feature of our study is the absence of any deaths that contrasts with the reported 28% mortality (eight streptococcal cases) in the BPSU study, which had similar rates of intensive care admission, inotropic and ventilator support 8. Compared with the BPSU study, in addition to the use of ECMO, adjunctive treatment was used more frequently in the patients in our study (clindamycin 56/62 (90%) vs 33/49 (67%), p=0.004; IVIG 30/62 (48%) vs 10/49 (20%), p=0.003) 8.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The most striking feature of our study is the absence of any deaths that contrasts with the reported 28% mortality (eight streptococcal cases) in the BPSU study, which had similar rates of intensive care admission, inotropic and ventilator support 8. Compared with the BPSU study, in addition to the use of ECMO, adjunctive treatment was used more frequently in the patients in our study (clindamycin 56/62 (90%) vs 33/49 (67%), p=0.004; IVIG 30/62 (48%) vs 10/49 (20%), p=0.003) 8.…”
Section: Discussioncontrasting
confidence: 59%
“…Compared with the BPSU study, in addition to the use of ECMO, adjunctive treatment was used more frequently in the patients in our study (clindamycin 56/62 (90%) vs 33/49 (67%), p=0.004; IVIG 30/62 (48%) vs 10/49 (20%), p=0.003) 8. Conversely, compared with our study, FFP was used more frequently in the patients in the BPSU study (15/62 (24%) vs 20/49 (40%), p=0.07) 8. FFP has substantially lower concentrations of antibodies compared with IVIG and has no proven anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Group A Streptococcus causes a severe illness with similarities to the staphylococcal toxic shock syndrome, occurring in both children and adults, associated with invasive group A streptococcal disease [33]. Patients with this syndrome present acutely with high fever, erythematous rash, mucous membrane involvement, hypotension, and multiorgan failure [34,35].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…In this month's edition, Adalat and colleagues1 report the results from a British Paediatric Surveillance Unit study of TSS in the UK and RI.…”
mentioning
confidence: 99%